Marknadsföring av lokal mat - Levrén, David (2008)
The process of food production has changed dramatically over the past one hundred years. Industrialization has led to large units of production, manufacturing, distribution, marketing and retail business. The final food product, in this system, is quite often fairly anonymous and the consumer will most likely know very little concerning the origin of the product. In recent years, the market for locally produced food has grown. There is an increasing interest in and demand for locally produced food items.